Journey to the West: Malay(si)an women's narratives of travels in England, 1934-58 - Ahmad, Siti Nuraishah (IIUM Journal Publication Unit, 2020)
Abstract: This paper examines two texts by Malay(si)an women: Aishah Ghani’s Ibu Melayu Mengelilingi Dunia (1956) and P.G. Lim’s memoirs, Kaleidoscope (2012). It focusses on the narratives of their journeys to and in England between 1934 and 1958. P.G. Lim (1915-2013) and Aishah Ghani (1923-2013) were contemporaries who lived in Malaya under British colonial rule, participated in nationalist movements for Malaya’s independence, and served in the post-colonial government of Malaya and Malaysia in pioneering roles. Their journeys to England took place before the Second World War and after. Their travel narratives provide readers with valuable insight into the rapidly changing roles of Malay(si)an women within a span of twenty-five years. Lim’s and Aishah’s travels to England in the waning days of the British Empire reveal their experiences and observations of the imperial centre, and the significance of these to their notions of women’s freedom of movement and independence from colonial rule. Informed by the work of Inderpal Grewal on Indian female travellers to the West, this paper aims to address the limited research on the history of female mobility, travel, and travel writing in Malay(si)a.